The Involvement of the Kingdom of Buleleng, Hinduism, and Islam: Observation of the Art and Ideology of the Architectural Gate of the Great Mosque of Jami' Singaraja - Luhuringbudi, Teguh (Balai Diklat Keagamaan Denpasar, 2024)
The study aims to reveal the intricate process of integration and collaboration between the Kingdom of Buleleng, Hinduism and Islam, evident in the Great Mosque of Jami' Singaraja gate's design. The paper employs a logical and concise structure that includes common academic sections, ensuring clear and necessary information flow and causal connections between statements. The language is objective, value-neutral, and free from biased, emotional or ornamental language, keeping a formal register throughout. The research employs precise subject-specific vocabulary and adheres to grammatical correctness, conventional structure, clear and logical structure, and balanced assessment. The aim was achieved using three methods: first, the Aditya Wardana gate architectural method examined the aesthetic nuances and significance of the extrinsic layers connected to the construction of the gate under study; second, the semiotic method proposed by Riffaterre established the implied meanings of the physical form of the gate in question; and third, the ideological method was used to analyze the results of the first two methods to provide a more comprehensive interpretation of the explicit and implied meanings. This study concludes that the gate architecture of the Great Mosque of Jami' Singaraja contributes to the negotiation between environmental sensitivity and cultural beautification ethics. This can be observed through three findings: a) a symbol of social status that values responsible pluralism, the obligation to present joy, maintaining expressive values, and dissolving negative elements; b) a reminder of guidelines for social life, inner purity, and psychological wisdom; and c) an ideology of togetherness for the Muslim profile, which must pay attention to inclusive personality, mass mobilization for social care, and the reproduction of individual piety.